The cooperation between European Union and the African, Caribbean and the Pacific countries. From a political anthropology perspective. - (:unkn) unknown (My University, 2016)
The cooperation between European Union and the African, Caribbean and the Pacific (ACP) countries did not allow the ACP countries to reach their development goals and the end of Cotonou agreements in 2020 is fast approaching. The aim of this thesis is to go beyond the analysis of European development programs to show the logics, processes, contradictions at play in the field of cooperation as well as the representations of the actors.This work falls within the framework of a political anthropology perspective in order to bring forth new elements for a better understanding of the cooperation between European Union and the ACP countries.
Keywords: African Research